Recent applications of porphyrins as photocatalysts in organic synthesis: batch and continuous flow approaches - Costa e Silva, Rodrigo; Oliveira da Silva, Luely; de Andrade Bartolomeu, Aloisio; Brocksom, Timothy John; de Oliveira, Kleber Thiago (Beilstein Journal of Organic Chemistry, 2020)
In this review we present relevant and recent applications of porphyrin derivatives as photocatalysts in organic synthesis, involving both single electron transfer (SET) and energy transfer (ET) mechanistic approaches. We demonstrate that these highly conjugated photosensitizers show increasing potential in photocatalysis since they combine both photo- and electrochemical properties which can substitute available metalloorganic photocatalysts. Batch and continuous-flow approaches are presented highlighting the relevance of enabling technologies for the renewal of porphyrin applications in photocatalysis. Finally, the reaction scale in which the methodologies were developed are highlighted since this is an important parameter in the authors’ opinion.
Keywords: energy transfer; photocatalysis; photooxygenation; photoredox; porphyrins